Teacher education around the world : changing policies and practices - Darling-Hammond, Linda, 1951-; Lieberman, Ann. (Milton Park, Abingdon, Oxon : Routledge, 2011)
'Teachers are the most important single element of the education system but what does it take to create high quality teachers in today's world? Around the world, countries are struggling to understand how to change their schools to meet global demands. International comparisons have shown that schools in Finland lead the league tables, but why is this, what new policies and practices in teacher education have they developed and how do they support the changes? A number of European and Asian countries also top the list when it comes to providing high quality teacher education, but there is little information about what and how they are doing the work and how they have made changes. The leading international contributors to this book describe the systemic policies and practices of teacher education in eight high-achieving countries and how they are dealing with teacher quality, equity, and the changing global society. Among the countries that are doing well - Finland, Singapore, the Netherlands, the UK, Hong Kong, Canada, Australia and the USA - there is an interesting diversity of policies and practices that support their changes in education, including: - emphasis on the preparation, induction, support and assessment of new teachers - focus on teacher retention, teachers' professional knowledge and continuing professional development - curriculum change and critical policies'--
Includes index and references : p.173 -193.
Keywords: Teachers -- Training of -- Cross-cultural studies; Education and state -- Cross-cultural studies; Educational change -- Cross-cultural studies